Effect of ionic compositions in nasal irrigations on human olfactory thresholds. (30th September 2014) - Lam, Kent; Conley, David B.; Liu, Kevin; Kern, Robert C.; Tan, Bruce K.; Richter, Claus‐Peter
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Nasal irrigations are commonly employed to promote nasal hygiene in the treatment of various sinonasal conditions. Few studies have evaluated how the ionic composition of irrigation solutions affects olfactory performance. The purpose of this study was to determine the dose responsiveness of human olfactory thresholds for each of the following ions: potassium, sodium, and calcium. Study Design Prospective translational study. Methods Irrigation solutions with variable potassium, sodium, and calcium were tested in 25 healthy human participants. Six potassium concentrations (range, 2–10 mM), six sodium concentrations (range, 73.7–113.7 mM), and three calcium concentrations (range, 0.44–0.64 mM) were used. Before and immediately following irrigations, olfactory thresholds were determined using the Sniffin' Sticks test. Differences in olfactory threshold scores before and after irrigations were compared to assess the effect of ionic composition on olfactory sensitivity. Results Physiologic concentrations of potassium, sodium, and calcium at 5.7, 89.5, and 0.54 mM, respectively, did not significantly change olfactory thresholds. Variations in both potassium and sodium concentrations demonstrated statistically significant dose‐dependent elevations in olfactory thresholds (P < .05). Only the calcium concentration that was lower than the physiologic level led to significant elevations in olfactory thresholds. Conclusions Different potassium and sodium concentrations in irrigation solutions provide distinctive dose‐dependent shifts in olfactory thresholds. Calcium concentrations also elevate olfactory thresholds, but calcium plays a less significant role than potassium and sodium in modulating olfactory thresholds. These results highlight the importance of the intranasal ionic microenvironment in olfactory physiology and suggest that optimal ionic concentrations in irrigation solutions exist to preserve olfactory function. Level of Evidence NA Laryngoscope, 125:E50–E56, 2015